Pengaruh Pertumbuhan Penjualan, Struktur Modal, Leverage, Likuiditas dan Ukuran Perusahaan Terhadap Kinerja Keuangan - Salsa Ramadina; Erma Setiawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of sales growth, capital structure, leverage, liquidity, and company size on financial performance of industrial sector companies listed on the Indonesia Stock Exchange (IDX) during the period of 2018-2022. The research uses a quantitative approach with multiple linear regression analysis, utilizing secondary data obtained from companies' annual financial statements. The results indicate that sales growth, capital structure, leverage, and liquidity do not significantly affect the financial performance of companies. However, company size has a proven effect on financial performance in the industrial sector companies during the analyzed period. This study provides new insights into factors influencing financial performance in Indonesia's industrial sector, despite limitations in the number of independent variables used.